Consumer preference on celebrity endorsement the case of Perodua / Izzah Raynie - Raynie, Izzah (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2013)
The purpose of this study is to identify the most important factors when deciding on celebrity endorser and to investigate which celebrity that would be the most credible celebrity to endorse PERODUA’s advertisement. This study are involved PERODUA 's prospect and customer in Kota Kinabalu, by using questionnaire this research will investigate the most important factors when deciding on celebrity endorser and which celebrity that would be the most credible to endorse PERODUA 's adve11isement. The result showed that the most credible celebrity to endorse PERODUA’s advertisement are sports celebrity and the most important factors when deciding on celebrity endorser are attractiveness. TEARS model are the independent variable for this study overall from 120 respondents choose attractiveness to be the most important factors when deciding on celebrity endorsement and sports celebrity become the most credible celebrity to endorse PERODUA advertisement.